AYURVEDIC MANAGEMENT OF HANUSTAMBHA: A CASE STUDY - *Malini Moger; S.N.Belavadi (International Journal of Ayurveda and Pharma Research, 2019)
Life without movement is impossible to think of in a healthy person’s normal life. Hanugraha or Hanustambha is one of the commonest problem affects irrespective of sex, age and socioeconomic status etc. The disease has the symptoms like stiffness of jaw with or absence of pain. The symptoms are seen suddenly with chronic Nidana Sevana. Jaw dislocation occurs when the lower part of the jaw moves out of its normal position. Temporomandibular joint disorder can cause pain, abnormal joint movements and joint noises. The life time incidence of Temporomandibular joint disorder is more than 10 million cases per year in India. In Hanugraha, Vata is predominantly involved. Here an attempt is made on Hanustambha with Ayurvedic management.